Use and Effect of Si/Silica Nano Materials in Polyurethane's Structure - SHOKUHI RAD, A.; ARDJMAND, M. (Asian Journal of Chemistry, 2010)
Polyurethanes are functional polymers whose properties can be tailored made by simply adjusting the compositions to meet the highly diversified demands of modern technology. The assembly of inorganic-organic nanocomposite materials affords unique opportunities to create revolutionary material combinations. These novel materials can have unexpected properties arising from the synergism between the components. More and more attention is being paid to the incorporation of an inorganic network such as a silica phase into an organic polymer matrix because of the potential physical and chemical properties. In the past decade, material scientists showed great interest in organic-inorganic nanocomposites as their application could dramatically improve material properties such as heat resistance, radiation resistance, mechanical and electrical properties and other properties in engineering plastics, enhanced rubber, coatings and adhesives. The properties of nano-composites strongly depend on the organic matrix, nanoparticles and the way in which they were prepared. Many researchers studied organic/inorganic nanocomposite systems and tried to understand the mechanism so as to obtain the expected improvement over traditional organic materials. It was founded that nano-silica could increase the hardness and scratch resistance of a coating and keep it clear at the same time. Nano-silica could enhance tensile strength and elongation of polyurethanes elastomer, although the modulus and hardness were lower than the corresponding microsize filled polyurethanes.